Occupational UV-Exposure is a Major Risk Factor for Basal Cell Carcinoma: Results of the Population-Based Case-Control Study FB-181. Issue 1 (January 2018) - Schmitt, Jochen; Haufe, Eva; Trautmann, Freya; Schulze, Hans-Joachim; Elsner, Peter; Drexler, Hans; Bauer, Andrea; Letzel, Stephan; John, Swen Malte; Fartasch, Manigé; Brüning, Thomas; Seidler, Andreas; et al.
Abstract : Objective: The aim of this study was to investigate the role of occupational and nonoccupational ultraviolet (UV)-exposure concerning the development of basal cell carcinoma (BCC). Methods: We undertook a population-based multicenter case–control study. Patients with first incident BCC ( n  = 836) were propensity score matched by age and sex to controls without skin cancer ( n  = 836). Sociodemographic characteristics, clinical characteristics, and lifetime UV-exposure were assessed by trained investigators. The differential estimation of occupational and nonoccupational UV-exposure dosages was based on validated instruments and established reference values. Associations were assessed using multivariable-adjusted conditional logistic regression models. Results: Individuals with high levels of occupational UV-exposure were at significantly increased BCC-risk compared with individuals with low [odds ratio (OR) 1.84; 95% confidence interval (95% CI) 1.19 to 2.83 and moderate (OR 1.97; 95% CI 1.20 to 3.22) occupational UV-exposure. Nonoccupational UV-exposure was not independently associated with BCC. Conclusion: Skin cancer prevention strategies should be expanded to the occupational setting.